AN EXPLORATION OF THE VARIABLES THAT HELP CREATE MAQASID AL-SHARI’AH BASED FINANCIAL INSTITUTIONS DEVELOPMENT INDEX - Azam Ali; Tanveer Kishwar (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2017)
Maqasid al-shariah can be defined as the objectives of Islamic law. The two main sources that can be considered as the core of Islamic law are Al-Quran and Sunnah. Maqasid al-shariah objectives are based on their constituent part of the goals and objectives which constituted the reasons for legislation of the rule of Islam. Imam Al-Ghazali classified maqasid into five major categories viz. faith, self, intellect, posterity, and wealth. The details on the description of these objectives are essential to achieve the study goal and to support the shariah purpose for the welfare of human beings. Al-maqasid al-shariah is an important and yet somewhat neglected science of the Shariah. Presently, in Muslim countries, the maqasid have become the focus of attention to provide convenient access to Shariah. This can be achieved with the development of a framework that can help in creating maqasid al-shariah based financial institutions’ development index. This study aims to explore the measurable of Al-Maqasid al-Shari’ah by suggesting various indicators that discover their nexus with financial institution parameters and help develop a framework. The study identifies that most of the countries prepare data on conventional and Islamic financial institution that can be mapped with Al-Maqasid al-Shari’ah five major categories. To help create a generalized index, the study provides few countries’ web addresses to acquire data on the identified measurable to achieve this objective. =========================================== Maqasid al-syariah dapat didefinisikan sebagai tujuan hukum Islam. Dua sumber utama yang dianggap sebagai inti dari hukum Islam adalah Al-Quran dan Sunnah. Tujuan Maqasid al-syariah didasarkan pada pentingnya tujuan dan sasaran yang menjadi dasar bagi peraturan dan perundang-undangan menurut Islam. Imam Al-Ghazali mengklasifikasikan maqasid dalam lima kategori utama yaitu, iman, diri sendiri, kecerdasan, keturunan dan kesejahteraan. Penjelasan rinci tujuan ini penting untuk mencapai tujuan kajian guna mendukung tujuan syariah bagi kesejahteraan manusia. Al-maqasid al-syariah adalah ilmu penting namun terabaikan dalam syariah. Saat ini, di negara-negara Muslim, maqasid telah menjadi fokus perhatian untuk menyediakan akses mudah ke syariah. Hal ini dapat dicapai dengan pengembangan kerangka kerja yang dapat membantu dalam menciptakan maqasid al-syariah berdasarkan indeks pembangunan institusi keuangan. Penelitian ini bertujuan untuk mengeksplorasi pengukuran Al-Maqasid al-syariah dengan mengusulkan berbagai indikator-indikator yang mengungkapkan hubungannya dengan parameter institusi keuangan dan membantu pengembangan kerangka kerja. Studi ini mengidentifikasi sebagian besar negara yang menyediakan data institusi keuangan Islam dan konvensional yang dapat dipetakan menurut lima katagori Al-Maqasid al-Shariah. Untuk membantu membuat indeks umum, kajian menyediakan alamat web beberapa negara untuk memperoleh data pengukuran yang diidentifikasi untuk mencapai tujuan tersebut.